2006
DOI: 10.1080/10934520600966177
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Metal Oxide Nanoparticles in Mammalian Cells

Abstract: Along with existing and emerging use of nanoscale materials, growing concerns have arisen about their unintentional health and environmental impact. The objective of the ongoing study was to assess the toxicity profile of metal oxide nanoparticles proposed for use in industrial production methodology. Metal oxide nanoparticles used in this study included TiO2, ZnO, Fe3O4, Al2O3, and CrO3 with particle sizes ranging from 30 to 45 nm. Cellular morphology, mitochondrial function, membrane leakage of lactate dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
384
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 697 publications
(412 citation statements)
references
References 13 publications
23
384
0
5
Order By: Relevance
“…The reported cytotoxic zinc concentration, using different cell types, in culture is 150 µM, [32] which suggests that the amount of zinc released in our system is slow enough to not create adverse cellular effects due to the presence of zinc.…”
Section: Hydrolytic Degradation Of Films At 37 °Cmentioning
confidence: 80%
See 2 more Smart Citations
“…The reported cytotoxic zinc concentration, using different cell types, in culture is 150 µM, [32] which suggests that the amount of zinc released in our system is slow enough to not create adverse cellular effects due to the presence of zinc.…”
Section: Hydrolytic Degradation Of Films At 37 °Cmentioning
confidence: 80%
“…We first wanted to disregard the potential cytotoxicity of the system -some authors have reported that ZnO might be cytotoxic under certain conditions - [31][32][33] using a LIVE/DEAD ® assay. To do so, C2C12 were seeded onto the surfaces with growth medium for 1 week.…”
Section: Biocompatibility Cell Adhesion and Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Delouise reported that ZNPs are nontoxic to cultured human dermal fibroblasts [13]. Other reports suggest that these nanoparticles are toxic to neuroblastoma cells [14], vascular endothelial cells [15], liver and kidneys [16,17]. In present study, toxic effects of ZNP on the mouse spermatogenesis were investigated.…”
Section: Introductionmentioning
confidence: 79%
“…There is now a growing body of literature on the potential undesirable effects caused by the exposure to different types of ENMs (Horie & Fujita, 2011;Jeng & Swanson, 2006;Karlsson, Gustafsson, Cronholm, & Möller, 2009;Magrez, et al, 2006). Although the awareness of the potential adverse effects of ENMs is increasing, there are still numerous unanswered questions which complicate the appropriate evaluation of toxicity at the nano-scale dimension.…”
Section: Introductionmentioning
confidence: 99%